(untitled) (Research, Society and Development, 2022)
Objective: To describe the epidemiological profile of patients with Parkinson’s disease seen at the Physical Therapy and Occupational Therapy Teaching and Assistance Unit at the Centro Specialized em Reabilitação II in the State of Pará. Methods: This is an cross-sectional and retrospective study, with patients diagnosed with PD by spontaneous demand, the staging of the disease was measured through the Hoehn and Yahr scale modified version besides an evaluation form to collect data regarding the epidemiological profile related to the general health status of the patients. Results: The study included 25 patients of both sexes, aged between 45 and 80 years, mostly men (60%), with Hoehn & Yahr classified mainly as mild to moderate disability (84%) and severe disability (12%). The main comorbidities were systemic hypertension (44%), anxiety disorder (16%) and dyslipidemia (12%). As for the first symptoms, 40% of them developed some symptom in the age group between 45-50 years. As for drugs, most of them used Levodopa (72%) and Prolopa (48%). Conclusions: Most of the patients evaluated were elderly, above 60 years old, who presented symptoms from 45 years of age on, use several medications, which collaborate more and more with the appearance of physical and emotional alterations, and that, due to their age, increase the possibilities of other comorbidities related to the disease and/or aging. Studies that seek epidemiological information collaborate both for the knowledge of how the disease manifests itself and to study and prevent associated factors and other comorbidities.